THU0618-HPR PSYCHOSOCIAL CHANGES IN RHEUMATIC DISEASE: A NURSING LED CROSS-SECTIONAL STUDY. (2nd June 2020) - Spagnuolo, R.; Grembiale, R. D.; Iaquinta, F. S.; Funari, V.; Pagnotta, R.; Naty, S.; Doldo, P.
Abstract : Background: Nursing management in Rheumatic Diseases (RD) is focused on global patient care. Starting from basic knowledge of diagnostic and therapeutic management, nurses can assess the impact of RD on patients' quality of life not only at the physical level, but also at the psychological, social, and emotional levels. Objectives: To evaluate psycosocial changes in RD patients through nursing-led Patient-Reported Outcomes Methods: We performed a cross-sectional study of 100 RD patients compared with 100 healthy volunteers matched for age, sex and BMI. Specialist nurses invited patients and volunteers to complete questionnaires on quality of life through seven domains (anxiety, depression, fatigue, sleep disturbance, pain interference, physical functions and satisfaction with participation in social roles) of the Patient-Reported Outcomes Measurement Information System (PROMIS). Results: Among 100 RD patients, 52 (52%) had a diagnosis of Rheumatoid Arthritis; 17 (17%) had a diagnosis of axial spondylorthritis (Ankylosing Spondylitis and Psoriatic Artritis); 25 (25%) had connectivitis (i.e. Lupus, Systemic Sclerosis, Sjögren Syndrome), and finally 6 (6%) had vasculitis. Median disease duration was 7±5 years. Just under half (43%) of RD patients had active disease measured by specific disease activity index. As shown in table 1, no significant difference highlight between the two groups with regard to anthropompetric and demographic characteristics. We found that patients report significantly greater psychosocial changes than healthy controls. More specifically, as shown in figure 1A, mean T score for anxiety, depression, fatigue and sleep disturbances were significantly higher in the RD patients than in healthy controls (56 ± 9 vs 48 ± 8 p<0.001; 52 ± 9 vs 46 ± 8 p <0.001; 58 ± 8vs 48 ± 8 p <0.001; 52 ± 10 vs 44 ± 8 p <0.001) respectively. Moreover, also in the social dimension in terms of pain interference, physical functions and satisfaction with participation in social roles, patients showed a median T score worse than healthy controls (Fig.1B ). Conclusion: This exploratory study highlights the need to adopt validated questionnaires in clinical practice, and demonstrates that PROMIS is a valid, objective, and standardized instrument that can help nursing staff to better define the consequences of the disease in a patient's daily life. References: [1]Minnock P, McKee G, Kelly A, et al. Nursing sensitive outcomes in patients with rheumatoid arthritis: a systematic literature review.Int. J. Nurs. Stud., 77 (2017), pp. 115-129 [2]Bartlett SJ, Orbai AM, Duncan T, et al. Reliability and validity of selected PROMIS measures in people with rheumatoid arthritis. PloS One. 2015 Disclosure of Interests: None declared